2016
DOI: 10.1364/oe.24.020621
|View full text |Cite
|
Sign up to set email alerts
|

How an oxide shell affects the ultraviolet plasmonic behavior of Ga, Mg, and Al nanostructures

Abstract: Abstract:The ultraviolet (UV) range presents new challenges for plasmonics, with interesting applications ranging from engineering to biology. In previous research, gallium, aluminum, and magnesium were found to be very promising UV plasmonic metals. However, a native oxide shell surrounds nanostructures of these metals that affects their plasmonic response. Here, through a nanoparticle-oxide core-shell model, we present a detailed electromagnetic analysis of how oxidation alters the UV-plasmonic response of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 34 publications
4
72
0
Order By: Relevance
“…As a consequence, plasmonic resonances of Al NPs are spectrally modified. It has been experimentally and theoretically shown that the growth of this oxide layer leads to both a red-shift and a weakening of the resonance peaks in Al NPs with different shapes [22,23,31,34]. On the other hand, the self terminating oxide layer can prevent further oxidation, producing a natural encapsulation.…”
Section: Aluminummentioning
confidence: 99%
See 3 more Smart Citations
“…As a consequence, plasmonic resonances of Al NPs are spectrally modified. It has been experimentally and theoretically shown that the growth of this oxide layer leads to both a red-shift and a weakening of the resonance peaks in Al NPs with different shapes [22,23,31,34]. On the other hand, the self terminating oxide layer can prevent further oxidation, producing a natural encapsulation.…”
Section: Aluminummentioning
confidence: 99%
“…However, the oxidation of Mg NPs is more aggressive. The native oxide MgO forms without stopping upon exposure to air as oxygen rapidly diffuses through porous oxide into the metal [15,23]. This process leads to a complete destruction of the plasmonic effects on Mg NPs, unless they are manipulated under controlled atmospheres [49].…”
Section: Magnesiummentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent months, Gutierrez et al reported an investigation of the effect of an oxide shell on the ultraviolet plasmonic behavior of Ga, Mg, and Al nanostructures. They studied the plasmonic response of Mg/MgO nanostructures and effect of oxidation on the UV-plasmonic response of Mg/MgO spherical or hemisphere-on-substrate nanostructures [22].…”
Section: Introductionmentioning
confidence: 99%